Experiences and specificities of school violence in the perception of employees of a public school - Netto, Luciana (2013)
Objective: to understand the experience and specificities episodes of violence at school, regarding the statement of employees of a school in the town of Divinópolis-MG. Method: we used the qualitative method, and the data collected through semi-structured interviews. Data were analyzed by content analysis. Results: for the staff, the educational institution is the subjection of a disorder that has been disseminating and making his main character weakness. Involving all school staff, violence enters the quality of service thereof, with effects on their stories of violence as witnesses, victims and/or listeners. Conclusion: the study shows that violence has multifactorial origins. The focus of these interventions includes reducing the inappropriate behavior of students and enable/strengthening of the behavior of employees and other member of the school environment